Purposeful cryopreservation of sperm prior to intrauterine insemination to overcome the embryo implantation defect associated with sperm with a subnormal hypoosmotic swelling test - J.H. Check; D.L. Check; M.P. Dougherty; G. DiAntonio (IMR Press, 2020)
Purpose: To determine if the toxic protein causing sperm to have low hypoosmotic swelling (HOS) test score and subsequent embryo implantation defects caused by this abnormality is cryolabile, and thus possibly purposeful cryopreservation followed by intrauterine insemination (IUI) could result in a pregnancy. Materials and Methods: The etiologic factor for a two-year history of infertility failing to respond to IUI and two cycles of in vitro fertilization-embryo transfer (IVF-ET) using conventional insemination was found secondary to a very low HOS test (32% with abnormal < 50%). With IVF-ET with intracytoplasmic sperm injection (ICSI), the patient conceived in her first cycle but she had a miscarriage. She failed to conceive in cycle 2 (actually her 4th IVF-ET cycle). Treatment with the protein digestive enzyme chymotrypsin corrected the HOS defect (HOS test 75-80%) on 3 different treatment specimens but she failed to conceive despite IUI with treated sperm. She had switched to IUI for financial reasons. Unfortunately the manufacturer temporarily stopped making chymotrypsin. A unique treatment was attempted for the first time - cryopreservation of the sperm prior to IUI hoping the toxic protein was cryolabile. Results: A viable pregnancy was achieved following the first IUI cycle with frozen thawed sperm. Unfortunately there was fetal demise found to be secondary to trisomy 14. Conclusion: Sperm with low HOS tests do not inhibit fertilization but instead causes embryo implantation defects hypothesized to be related to the supernumerary sperm attached to the zona pellucida. This is the first reported case of a pregnancy achieved by IUI using cryopreserved sperm with low HOS scores.